2009
DOI: 10.1007/s10499-009-9310-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total phosphorus requirement of juvenile yellow catfish Pelteobagrus fulvidraco

Abstract: The present experiment was conducted to determine the dietary total phosphorus requirement of juvenile yellow catfish Pelteobagrus fulvidraco. Six diets with increasing dietary phosphorus concentration (0.43, 0.55, 0.78, 0.90, 1.05 and 1.18% of dry matter, respectively) were fed to triplicate groups of 20 fish each (mean initial body weight, 2.68 ± 0.08 g, mean ± SD) to apparent satiation for 7 weeks. Weight gain and specific growth rate (SGR) increased with increasing dietary phosphorus level from 0.43 to 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 33 publications
(64 reference statements)
11
37
0
1
Order By: Relevance
“…At present, different parameters have been used to determine mineral requirement in fish, including growth performance (Lin et al, 2010;Pan et al, 2008;Tan et al, 2011), feed utilization (Luo et al, 2010, tissue mineral concentration (Lin et al, 2008;Luo et al, 2010;Maage et al, 2000;Pan et al, 2008;Tan et al, 2011) and hepatic Mn-SOD activity (Lin et al, 2008). Our present study indicated that Mn requirements obtained from WG, PER and hepatic Mn-SOD activities were similar, whose values were 5.5, 5.6 and 6.4 mg kg − 1 diet, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…At present, different parameters have been used to determine mineral requirement in fish, including growth performance (Lin et al, 2010;Pan et al, 2008;Tan et al, 2011), feed utilization (Luo et al, 2010, tissue mineral concentration (Lin et al, 2008;Luo et al, 2010;Maage et al, 2000;Pan et al, 2008;Tan et al, 2011) and hepatic Mn-SOD activity (Lin et al, 2008). Our present study indicated that Mn requirements obtained from WG, PER and hepatic Mn-SOD activities were similar, whose values were 5.5, 5.6 and 6.4 mg kg − 1 diet, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, in our laboratory, studies have been conducted to determine several mineral requirements for the fish species, including dietary phosphorus (Luo et al, 2010), copper and zinc requirement . We also evaluated the effect of dietary cadmium levels (Tan et al, 2010b) on growth performance and hepatic intermediary metabolism for this fish species.…”
Section: Introductionmentioning
confidence: 99%
“…However, 107 days of late P deficiency did not affect final length and weight significantly (Deschamps et al 2014). The initial body weight in the present study was about 40~45 g, while in many of the previous studies, fish used in the experiments were less than 10 g (Roy & Lall 2003;Mai et al 2006;Zhang et al 2006;Shao et al 2008;Sukumaran et al 2009;Luo et al 2010;Xie et al 2011;Yuan et al 2011;Liang et al 2012;Yu et al 2013), which should be more sensitive to P supplement. Thirdly, a relatively low growth rate may result in low P requirement, for rapid growing fishes had higher diet P requirement (Benstead et al 2014) .…”
mentioning
confidence: 50%
“…The inflection point of the selected logistic model indicates the maximum change rate of dissolved P waste discharge relative to dietary P avail% occurring at P avail% = 1.00 and dissolved P waste = 5 g kg -1 feed, probably denoting the maximum activity levels of both the passive diffusion and active transport absorption and the minimum level of renal reabsorption rate. According to the previous studies (Luo et al 2010;Tang et al 2012 meeting the metabolic requirements of juvenile yellow catfish. However, more investigation should be done to test this hypothesis, for example, using isotope-labeled techniques to measure the absorption rate of P in intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Yellow catfish (Pelteobagrus fulvidraco), a freshwater species native to Asian-Pacific waters, is one of major commercial species and extensively cultured in aquaculture farms in China, The nutritional requirement for phosphorus content in their diet is important for their survival and growth during the juvenile stages (Luo et al 2010;Tang et al 2012). In this study, we use juvenile yellow catfish as an example to (1) investigate how dietary phosphorus level influences P wastes; (2) develop the AIC-selected empirical models for phosphorus metabolism; (3) discuss the potential mechanisms driving phosphorus metabolism in fish species.…”
Section: Aquacult Intmentioning
confidence: 99%